2015
DOI: 10.1177/1049732315589095
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Not Like You Need to Live 10 or 20 Years”

Abstract: The literature suggests that the patient-perspective approach (i.e., eliciting and responding to patients' perspectives, including beliefs, preferences, values, and attitudes) to patient-centered care (PCC) is not a reliable predictor of positive outcomes; however, little is known about why the patient-perspective approach does not necessarily lead to positive outcomes. By using discourse analysis to examine 44 segments of oncologist-patient interactions, we found that providers' use of patient-perspective con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Preliminary reading of all transcripts was undertaken to get an initial sense of the data and to identify issues for further consideration. We used a direct approach to coding and analysis where specific themes were already arranged as guided by literature [ 30 ]. However, the researchers allowed for additional new and relevant themes and subthemes to emerge during the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary reading of all transcripts was undertaken to get an initial sense of the data and to identify issues for further consideration. We used a direct approach to coding and analysis where specific themes were already arranged as guided by literature [ 30 ]. However, the researchers allowed for additional new and relevant themes and subthemes to emerge during the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…By building on social constructionism, IFADIA has an affinity with other social constructionist approaches to reflexive action research (e.g., Cunliffe, 2002;Ripamonti et al, 2016;Shotter, 2010). It also shares with other social constructionist research on knowledge production in health care a focus on knowing as a social activity taking place in the negotiation of meaning in communication processes in specific contexts of practice (e.g., Hsieh et al, 2016;Liberati et al, 2015;Quinlan, 2009).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Several studies of patient-centeredness describe a gap between the policy goals and practice, suggesting that the policy principle of patient-centeredness is difficult to implement in practice (Applequist et al, 2017;Franklin et al, 2019: Gardner & Cribb, 2016Hsieh et al, 2016;Lord & Gale, 2014). A number of researchers point to the multiple meanings and lack of a clear, common definition of patient-centeredness as a factor underlying implementation problems (Eklund et al, 2019;Langberg et al, 2019;Lord & Gale, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that identity work intersects with clinical decision making, as physicians will often reconcile tensions in patient communication by favoring an allegiance to their expert identities over the patient relationship (Yagil & Medler-Liraz, 2014). Another study reported that, in delivering patient-centered care through the perspective-taking approach, physicians used discursive tactics to dissuade the patient from committing an initial treatment decision in opposition to their therapeutic recommendation (Hsieh, Bruscella, Zanin, & Kramer, 2016). Our findings also suggest that surgeons lack sufficient clinical time for opioid-prescribing conversations and must expedite the achievement of competing goals in pain management communication.…”
Section: Discussionmentioning
confidence: 99%